Liver transplantation for advanced liver-only colorectal metastases. Issue 12 (12th June 2021) - Dueland, S; Syversveen, T; Hagness, M; Grut, H; Line, P-D
Abstract : Liver transplantation provided a 5-year overall survival rate of 100 per cent in patients with colorectal cancer who had undergone liver resection previously. Patients with extensive liver metastases (over 20 lesions) and a left-sided primary tumour had long survival, whereas those with an ascending colonic primary tumour had inferior survival after liver transplantation.